Observation of non-thermal electron formation during the thermal quench of shattered pellet injection shutdowns in DIII-D. (30th November 2020) - Hollmann, E.M.; Shiraki, D.; Baylor, L.; Bykov, I.; Eidietis, N.W.; Golovkin, I.; Herfindal, J.L.; Lvovskiy, A.; McLean, A.; Moyer, R.A.; O'Gorman, T.; Parks, P.B.; et al.
Abstract: Formation of non-thermal (hot) electrons is studied during the thermal quench of shattered pellet injection (SPI) discharge shutdowns in the DIII-D tokamak. Both pure neon and mixed neon/deuterium shutdowns are studied. High-energy radiation (SXR and EUV) brightness levels show indications of non-thermal electron formation during the TQ. The non-thermal densities are of order 10 18 m −3 and non-thermal temperatures are estimated to be of order 10 keV. The non-thermal electrons appear to be mostly lost during the subsequent current quench, as no signal of relativistic runaway electrons is typically seen at the end of the current quench. The non-thermals appear to have an effect on the deposition profile of the SPI pellets, especially at the end of the TQ, due to increased pellet ablation.